Hospital Acquired Infections, Multidrug Resistant (MDR) Bacteria, Alternative Approaches to Antibiotic Therapy - Bostik, Pavel; Kolar, Milan (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Bacterial resistance to known and currently used antibiotics represents a growing issue worldwide. It poses a major problem in the treatment of infectious diseases in general and hospital-acquired infections in particular. This is in part due to the overuse and misuse of antibiotics in past decades, which led to the selection of highly resistant bacteria and even so-called superbugs - multidrug-resistant (MDR) bacteria. Nosocomial infections, particularly, are often caused by MDR bacterial pathogens and the treatment of such infections is very complicated and extensive, often leading to various side effects, including adverse effects on the natural human microbiome. At the same time, the development of novel antibiotics is lagging with very few new ones in the pipeline. Finding viable alternatives to treat such infections may help to overcome these therapeutic issues. This publication brings novel developments in the field of bacterial resistance, mainly in the hospital settings, adequate antibiotic therapy, and identification of compounds useful to battle this growing issue.